A Review of Language Curriculum Development in Multilingual Classrooms - Erwin Erwin; Ahmad Firdaus Mohd Noor (Yayasan Adra Karima Hubbi, 2024)
Integrated curriculum models in language teaching have gained prominence as educators seek to provide holistic, interdisciplinary learning experiences that improve both language proficiency and content knowledge. These models emphasize the meaningful application of language skills across various subjects, promoting deeper student engagement and critical thinking. However, the implementation of integrated curricula presents challenges related to teacher collaboration, resource availability, and institutional support, especially in traditional educational settings. This review aims to analyze the effectiveness of integrated curriculum models in language teaching by synthesizing findings from empirical studies and theoretical discussions. The study examines how these models influence language learning outcomes, foster critical thinking, and address the practical challenges faced by educators. Both qualitative and quantitative studies were included, covering various educational levels and cultural contexts. The findings indicate that integrated curriculum models enhance language proficiency, particularly in communicative and academic skills, while simultaneously improving student engagement and content mastery. Effective implementation depends on strong teacher collaboration and institutional support. However, barriers such as inadequate resources and lack of training often hinder the success of these models. In conclusion, integrated curriculum models offer substantial potential for improving language education, but their success requires careful planning and sufficient support. Future research should focus on long-term outcomes and the adaptation of these models to diverse educational contexts to maximize their impact.